Destabilizing Said’s Notion of Orientalism: A Critical Study of The Travels of Mirza Abu Taleb Khan (Pragyajyoti, 2024)
During the colonial period, many literary works helped the empire create a narrative about the Orient. However, few works describe the West from the perspective of the East. The Travels of Mirza Abu Taleb Khan is one such travelogue, offering a unique view of Europe through the eyes of an Eastern traveler. This paper examines Taleb Khan’s observations and opinions about Europeans and their culture. Using Edward Said’s concept of Orientalism as a framework, the paper argues that Taleb’s travelogue presents an Eastern discourse that challenges Said’s idea of Orientalism. This study contributes to a deeper understanding of cross-cultural perspectives and challenges traditional narratives about East-West relations. It highlights the importance of diverse viewpoints in shaping historical and literary discourses.